Managing crises before they happen what every executive and manager needs to know about crisis management - Mitroff, Ian I. (New York AMACOM, 2001)
"From tragic accidents to public relations fiascos, we live in an increasingly crisis-ridden society. In fact, half of the major industrial accidents of the past century occurred in the last 20 years. Incidents such as Bhopal and the Exxon Valdez have become embedded in our consciousness, cultural icons of the worst sort. Other crises, less devastating but with serious impact on their businesses, occur almost daily. Why is this--and what can be done to reverse this disturbing trend? According to Ian Mitroff, one of the world's leading experts on crisis management, the rise in the crisis rate is due to an ingrained "it-can't happen-to-us" mentality--which, in turn, leads to a total lack of preparedness for crises. His solution? Find out in Managing Crises Before They Happen. This fascinating book provides readers with a powerful framework that will help them: * Recognize the early warning signals that almost always precede a crisis * Focus on the big picture, not just the details * Avoid becoming either the victim or the villain in a crisis situation * Understand the importance of personal character, corporate culture, and thinking outside the box to effective crisis management * Learn from one crisis things that can prevent or ameliorate the next."
Includes bibliographical references Index.
Keywords: Crisis management. Communication in organizations. Strategic planning